Physical and numerical simulation of inter-fracture flooding in heterogeneous tight oil reservoirs - Yi Yang; Guangzhi Liao; Wei Xiong; Rui Shen; Jie Zhang; Qi Li; Shengzhou Wang; Jianzhong Zhang; Lingfang Tan; Guoyong Shao (Energy Reports, 2022)
The existing tight oil reservoirs are mainly developed after hydraulic fracturing of horizontal Wells with low recovery. Traditional enhanced oil recovery (EOR) methods are difficult to apply in tight reservoirs, because huff-puff drives oil to the distal end, water breakthrough exists in inter-well flooding, and ASP flooding cannot enter the small pore throat of the tight reservoir. A new EOR method of inter-fracture flooding is proposed. This method solves the problem that the injection water cannot enter the matrix in tight reservoir by inter-fracture flooding. Inter-fracture flooding reduces the distance between the injection and production ends and reduces the risk of water channeling. Inter-fracture flooding increases the pressure gradient during water flooding in the reservoir and establishes an effective water displacement system in the heterogeneous tight reservoir. In this paper, physical simulation experiments and numerical simulation are designed to study the EOR effect of inter-fracture water flooding in heterogeneous tight reservoirs. The results showed the following: (1) Inter-fracture asynchronous water flooding (IFAWF) can improve oil displacement efficiency by 6%–16% compared with inter-fracture synchronous water flooding (IFSWF). (2) Compared with IFSWF, IFAWF can greatly improve the oil displacement efficiency of the core with low permeability in the heterogeneous model by more than 20%. (3) Effective water sweep cannot be achieved by IFSWF, but can be achieved by IFAWF. (4) IFAWF established effective displacement in 0.1mD tight heterogeneous reservoir. Studies have shown that inter-fracture flooding can lower the reservoir development permeability threshold and will be an important EOR method for tight oil and shale oil in the future.